PPARα/γ-Independent Effects of PPARα/γ Ligands on Cysteinyl Leukotriene Production in Mast Cells - Masamichi Yamashita (PPAR Research)
Peroxisome proliferator-activated receptor (PPAR) α ligands (Wy-14,643, and fenofibrate) and PPARγ ligands (troglitazone and ciglitazone) inhibit antigen-induced cysteinyl leukotriene production in immunoglobulin E-treated mast cells. The inhibitory effect of these ligands on cysteinyl leukotriene production is quite strong and is almost equivalent to that of the anti-asthma compound zileuton. To develop new aspects for anti-asthma drugs the pharmacological target of these compounds should be clarified. Experiments with bone-marrow-derived mast cells from PPARα knockout mice and pharmacological inhibitors of PPARγ suggest that the inhibitory effects of these ligands are independent of PPARs α and γ. The mechanisms of the PPAR-independent inhibition by these agents on cysteinyl leukotriene production are discussed in this review.